Focal adhesion kinase (FAK) siRNA inhibits human hypertrophic scar by suppressing integrin α, TGF‐β and α‐SMA. (24th April 2014) - Chen, Rui; Zhang, Zhiliang; Xue, Zhujia; Wang, Lin; Fu, Mingang; Lu, Yi; Bai, Ling; Zhang, Dongqing; Fan, Zhihong
Abstract The effect of focal adhesion kinase (FAK) on suppressing scarring and the potential molecular mechanism underlying it has been investigated. Ten samples of human hypertrophic scars (HS) tissue cultured in vitro were transfected with FAK siRNA mediated by liposome. Quantitative real‐time PCR was used to detect the expression of integrin α, transforming growth factor‐β (TGF‐β), FAK and α‐smooth muscle actin (α‐SMA) after transfection. MTT assay was used as a measure of fibroblast proliferation. Flow cytometry and 3H‐proincorporation technique gave measurements of the cell cycle and the quantity of collagen synthesis, respectively. Expression of FAK was effectively blocked, accompanied by decreasing expression of integrin α, TGF‐β and α‐SMA in hypertrophic scars fibroblast (HSFB) cells. One to 4 h after transfection with FAK siRNA, proliferation of HSFB cells was strongly inhibited (P < 0.01), reaching a maximum at 48 h. The proportion of G1 cells was higher and the proportion of the S and G2 cells lower after transfection. The amount of collagen synthesis in HSFB cells decreased when HSFB cells were transfected for 48 h. RNA interference targeting the FAK gene can block the two abnormal signal transduction pathways mediated by the integrin and TGF‐β receptors that are responsible for hyperplasia and contracture of the scar, making FAK iRNA therapy a potentially effective approach in HS treatment.